Exploring factors associated with smokeless tobacco use among young people: A systematic scoping review. (1st November 2022) - Lund, Lisbeth; Bast, Lotus Sofie; Rubæk, Mette; Andersen, Susan
Abstract: Purpose: While smoking is declining among young people, smokeless tobacco use is increasing. Identifying who is using smokeless tobacco and why is essential in preventing smokeless tobacco use. This study aimed to comprehensively explore the factors of young people's use of smokeless tobacco in western countries and identify research gaps. Methods: We conducted a systematic scoping review of studies that examined factors associated with smokeless tobacco use among young people (ages 13–29) from western countries published between January 2011 and September 2021. Searches were conducted in CINAHL, Medline, and Scopus. Studies on adults, total tobacco use (i.e., did not differentiate between tobacco product types), dual and multiple uses of tobacco, and studies on smokeless tobacco cessation programs were excluded. Results: A total of 160 studies were included in this scoping review. The studies were primarily undertaken in the US and the Scandinavian countries, and the majority explored smokeless tobacco use without distinguishing between the specific types. Smokeless tobacco users were more likely to be male, non-Hispanic white, engaging in physical activity, and using other substances, including cigarettes and alcohol. The role of friends and family were identified as critical factors that were related to the use of smokeless tobacco. Conclusions: This scoping review suggests that preventative measures against smokeless tobacco use should focus on peer and family members' roles and that these measures may benefit from targeting males. Additional research, including systematic reviews on this area to validate the identified associated factors, would improve the understanding of smokeless tobacco use. Highlights: A scoping review was done to identify factors of young people's smokeless tobacco use. Males, whites, and physically active youth were more likely to use smokeless tobacco. Harm-perception beliefs and other substance use influenced smokeless tobacco use. The role of the family and friends was identified as influencing factors. Focusing interventions on the key factors could be beneficial in preventing use.